Safety and efficacy of l‐tryptophan produced by fermentation with Escherichia coli CGMCC 7.248 for all animal species. (28th February 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on l ‐tryptophan produced by fermentation with a genetically modified strain of Escherichia coli CGMCC 7.248 when used as a nutritional additive in feed and water for drinking for all animal species and categories. The production strain E. coli CGMCC 7.248 and its recombinant DNA were not detected in the final product. The product l ‐tryptophan, manufactured by fermentation with E. coli CGMCC 7.248, does not give rise to any safety concern with regard to the genetic modification of the production strain. l ‐Tryptophan produced by E. coli CGMCC 7.248 is safe for non‐ruminant target species. The use of unprotected l ‐tryptophan in ruminant feed should be avoided. l ‐Tryptophan produced by fermentation by E. coli CGMCC 7.248 is safe for the consumer. The level of endotoxins present in the product and its dusting potential indicate an inhalation risk for the user. l ‐Tryptophan produced by E. coli CGMCC 7.248 is not a skin or eye irritant but it is a dermal sensitiser. The use of l ‐tryptophan produced by E. coli CGMCC 7.248 in animal nutrition does not pose a risk to the environment. The product under assessment is regarded as an effective source of the amino acid l ‐tryptophan for all non‐ruminant species. For the supplemental l ‐tryptophan to be as efficacious in ruminants as in non‐ruminant species, it requires protection against degradation in the rumen.